Metabolic reprogramming in cancer: mechanistic insights from Drosophila - Kenneth Kin Lam Wong; Esther M. Verheyen (The Company of Biologists, 2021)
Cancer cells constantly reprogram their metabolism as the disease progresses. However, our understanding of the metabolic complexity of cancer remains incomplete. Extensive research in the fruit fly Drosophila has established numerous tumor models ranging from hyperplasia to neoplasia. These fly tumor models exhibit a broad range of metabolic profiles and varying nutrient sensitivity. Genetic studies show that fly tumors can use various alternative strategies, such as feedback circuits and nutrient-sensing machinery, to acquire and consolidate distinct metabolic profiles. These studies not only provide fresh insights into the causes and functional relevance of metabolic reprogramming but also identify metabolic vulnerabilities as potential targets for cancer therapy. Here, we review the conceptual advances in cancer metabolism derived from comparing and contrasting the metabolic profiles of fly tumor models, with a particular focus on the Warburg effect, mitochondrial metabolism, and the links between diet and cancer.